Chemical and Biochemical Mechanisms Underlying the Cardioprotective Roles of Dietary Organopolysulfides - Tocmo, Restituto; Liang, Dong; Lin, Yi; Huang, Dejian (Frontiers in Nutrition, 2015)
Foods that are rich in organosulfides are highly regarded for their broad range of functions in disease prevention and health promotion since ancient time yet modern scientific study, particularly clinical studies could not agree with traditional wisdom. One of the complexities is due to the labile nature of organosulfides, which are often transformed to different structures depending on the processing conditions. The recent evidence of polysulfides as H2S donor may open up a new avenue for establishing structure and health promotion activity relationship. To put this development into perspective, we carried out a review on the recent development on the chemistry and biochemistry of organopolysulfides with emphasis on their cardioprotective property. Firstly, we briefly surveyed the foods that are rich in polysulfides and their structural diversity. This is followed by in-depth discussion on the chemical transformations of polysulfides under various processing conditions. We further reviewed the potential action mechanisms of polysulfides in cardioprotection through a) hydrogen sulfide releasing activity; b) radical scavenging activity; and c) activity in enzyme inhibition and intervention of gene regulation pathways. Based on the literature trend, we can conclude that the emerging concept of organopolysulfides as naturally-occurring H2S donors is intriguing and warrants further research to establish the structure and activity relationship of the organopolysulfides as H2S donors.